2017
DOI: 10.3138/cpp.2016-068
|View full text |Cite
|
Sign up to set email alerts
|

Are Quebecers More Stressed Out at Work than Others? An Investigation into the Differences between Quebec and the Rest of Canada in Level of Work Stress

Abstract: Le stress au travail coû te cher et diminue la productivité. Or, les Québécois sont plus susceptibles de rapporter un niveau élevé de stress au travail que les autres Canadiens. Dans cet article, à l'aide de données de l'Enquête sur la santé dans les collectivités canadiennes couvrant les années 2003 à 2012, les auteurs étudient les déterminants du stress au travail. Les maladies chroniques, les problèmes de santé mentale et de mauvaises habitudes de vie contribuent à augmenter le stress au travail. Cependant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…This suggests that in France, men possibly rely on women to act as resources available for them at home, as suggested by existing literature on the gender division of labour (Kergoat, 2005), but not so in Quebec, where the introduction of universal childcare and incentives for women to remain in the labour market and for men to be more involved at home has had the effect of increasing demands on men, rather than reducing demands on women. This is consistent with previous research involving a comparison of Quebec with other, less egalitarian, Canadian provinces (Sedigh et al, 2017), which noted that more egalitarian gender policies may increase men's stress without reducing womens', and so may have the paradoxical effect of increasing the average stress level among its population. A possible interpretation is that in a social‐democratic welfare regime, the double burden of paid and non‐paid work in the telework context is equally shared by women and men, unlike a conservative welfare regime with more traditional gender roles, where teleworking men are shielded against this double burden by women (Kurowska, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that in France, men possibly rely on women to act as resources available for them at home, as suggested by existing literature on the gender division of labour (Kergoat, 2005), but not so in Quebec, where the introduction of universal childcare and incentives for women to remain in the labour market and for men to be more involved at home has had the effect of increasing demands on men, rather than reducing demands on women. This is consistent with previous research involving a comparison of Quebec with other, less egalitarian, Canadian provinces (Sedigh et al, 2017), which noted that more egalitarian gender policies may increase men's stress without reducing womens', and so may have the paradoxical effect of increasing the average stress level among its population. A possible interpretation is that in a social‐democratic welfare regime, the double burden of paid and non‐paid work in the telework context is equally shared by women and men, unlike a conservative welfare regime with more traditional gender roles, where teleworking men are shielded against this double burden by women (Kurowska, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…But contrary to our expectation, we also found that it is significantly stronger for men than for women in Quebec where we expected no difference. This can be possibly linked to the equality of involvement of men in the domestic sphere on a par with women in a social‐democratic, more egalitarian welfare regime (Sedigh et al, 2017). Where this is the case (i.e., in Quebec as per our study), men may become more sensitive to telework conditions for maintaining the link with their organization, whereas in France, poor working conditions faced by men may be compensated for by women acting as a buffer.…”
Section: Discussionmentioning
confidence: 99%
“…This threshold has been shown to be associated with clinical depression and self-harm ideation in community mental health populations (results available on request). We compared Quebéc with the rest of Canada because of known differences in mental health state of populations of these two geographic regions (15,16), which may be a result of cultural differences (i.e., Québec is mainly francophone while the rest of Canada is predominantly anglophone). For simplicity, we only used data from survey 1 for an initial logistic regression model given that the levels of depression, anxiety and loss of interest were stronger at this stage (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…I n Canada, nearly 30% of workers report experiencing high daily levels of stress at work. 1 Law enforcement officers (LEOs) represent one occupational group that is highly vulnerable to occupational stress. [2][3][4] Indeed, LEOs are frequently exposed to operational stressors (stressors associated with job performance) such as seeing dead bodies or severely injured individuals, interacting with physically or sexually abused children, or experiencing violent encounters.…”
mentioning
confidence: 99%
“…In Canada, nearly 30% of workers report experiencing high daily levels of stress at work 1 . Law enforcement officers (LEOs) represent one occupational group that is highly vulnerable to occupational stress 2–4 .…”
mentioning
confidence: 99%